Functional outcome study for operatively managed cases of rotator cuff tear: managed by mini open repair - Parikh, Kushal N.; Adodariya, Yogenkumar A.; Patel, Dhruv M. (International Journal of Research in Orthopaedics, 2025)
Background: Rotator cuff tears (RCTs) are common musculoskeletal injuries impacting quality of life due to pain and functional limitation. The mini-open repair technique offers an alternative to arthroscopic repair with high success and accessibility. Objective of this study was to evaluate anatomical and functional outcomes of mini-open repair for rotator cuff tears. Methods: A prospective observational study was conducted on 30 patients operated by mini-open rotator cuff repair at a tertiary care hospital between 2022–2024. Preoperative and postoperative evaluations included ROM, UCLA score, and VAS at six months follow-up. Results: Mean age was 54.1 years, with male predominance. Dominant limb was involved in 67%. Significant improvements were observed in abduction (mean 76.7° to 147.1°), forward flexion (82.2° to 157.2°), external rotation (28.7° to 56.3°), and internal rotation. Mean UCLA score improved from 13.4 to 31.2 (p<0.001). Conclusions: Mini-open rotator cuff repair offers excellent pain relief, improved range of motion, and patient satisfaction in the short term. It remains a viable and effective option, especially in resource-limited settings.